Synthesis, antimalarial properties and 2D-QSAR studies of novel triazole-quinine conjugates. Issue 16 (15th August 2016) - Faidallah, Hassan M.; Panda, Siva S.; Serrano, Juan C.; Girgis, Adel S.; Khan, Khalid A.; Alamry, Khalid A.; Therathanakorn, Tanya; Meyers, Marvin J.; Sverdrup, Francis M.; Eickhoff, Christopher S.; Getchell, Stephen G.; Katritzky, Alan R.
Graphical abstract: Highlights: Designed and synthesized a set of triazole containing quinine conjugates. Synthesized conjugates shows promising antimalarial activity. 2D-QSAR studies supports the biological data. Developed QSAR model could be useful tool for new drug development. Abstract: Click chemistry technique led to novel 1, 2, 3-triazole-quinine conjugates8a –g, 10a –o, 11a –h and13 utilizing benzotriazole-mediated synthetic approach with excellent yields. Some of the synthesized analogs (11a, 11d –h ) exhibited antimalarial properties against Plasmodium falciparum strain 3D7 with potency higher than that of quinine (standard reference used) through in vitro standard procedure bio-assay. Statistically significant BMLR-QSAR model describes the bio-properties, validates the observed biological observations and identifies the most important parameters governing bio-activity.